2022
DOI: 10.1101/2022.05.04.22274692
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The spread and burden of the COVID-19 pandemic in sub-Saharan Africa: comparison between predictions and actual data and lessons learned

Abstract: Introduction Sub-Saharan Africa (SSA) was predicted to be severely affected by the coronavirus disease 2019 (COVID-19) pandemic, but the actual data seem to have contradicted these forecasts. This study attempted to verify this observation by comparing predictions against actual data on the spread and burden of the COVID-19 pandemic in SSA. Methods Focused on the period from March 1 st to September 30 th , 2020, we compared (1) the predicted interval dates when each SSA country would report 1 000 and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Since the beginning of the pandemic, misinformation has been shared on social media that claims COVID-19 is a planned strategy nefariously designed to control the world population, especially in Africa [ 20 , 23 ]. This thesis gained massive attention when the WHO predicted on 17 April 2020 that Africa would become the next epicenter of the COVID-19 pandemic [ 24 ]. A similar refractory attitude to the one we have reported towards the COVID-19 vaccines was reported in Cameroon by Ajonina-Ekoti et al before the vaccination campaign, where about 87% of the 591 participants reported their unwillingness to receive a COVID-19 vaccine if it was available in the country [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of the pandemic, misinformation has been shared on social media that claims COVID-19 is a planned strategy nefariously designed to control the world population, especially in Africa [ 20 , 23 ]. This thesis gained massive attention when the WHO predicted on 17 April 2020 that Africa would become the next epicenter of the COVID-19 pandemic [ 24 ]. A similar refractory attitude to the one we have reported towards the COVID-19 vaccines was reported in Cameroon by Ajonina-Ekoti et al before the vaccination campaign, where about 87% of the 591 participants reported their unwillingness to receive a COVID-19 vaccine if it was available in the country [ 25 ].…”
Section: Discussionmentioning
confidence: 99%